SEXUAL EDUCATION: WORKING WITH CHILDREN AND TEENS - Ribeiro, Marcos (2007)
With opinative text, present a brief history of Sexual Education as well as they teach how to work with children, teenagers and parents. The article also shows how to devellop an specific class, interconnecting subjects and last but not least introduces to the reader aspects of the Brazilian law and the patterns on the educative work in the fields of Sexuality and Prevention.